Impact of beta-blockade premedication on image quality of ECG-gated thoracic aorta CT angiography. (December 2014) - Entezari, Pegah; Collins, Jeremy; Chalian, Hamid; Tore, Huseyin Gurkan; Carr, James; Yaghmai, Vahid
Background: Thoracic aortic aneurysm is one of the most common aorta pathologies worldwide, which is commonly evaluated by computed tomography angiography (CTA). One of the routine methods to improve the image quality of CTA is heart rate reduction prior to study by beta-blockade administration. Purpose: To assess the effect of beta-blockade on image quality of the ascending aorta in electrocardiography (ECG)-gated dual-source CTA (DSCTA) images. Material and Methods: In this retrospective study, ECG-gated thoracic aorta CTA images of 40 patients without beta-blocker administration were compared with ECG-gated images of 40 patients with beta-blockade. Images of the aorta were analyzed objectively and subjectively at three levels: sinus of Valsalva (sinus), sinotubular junction (STJ), and mid ascending aorta (MAA). Quantitative sharpness index (SI) and signal-to-noise ratio (SNR) were calculated and two radiologists evaluated the image quality using a 3-point scale. Results: Mean heart rate in beta-blocker and non-beta-blocker groups was 61.7 beats per minute (bpm) (range, 58.1–63.9 bpm) and 72.9 bpm (range, 69.3–84.1 bpm), respectively ( P  <0.05). Aorta wall SI, SNR, and subjective grading were comparable between the two groups at all three levels ( P  >0.05). Conclusion: Beta-blocker premedication may not be necessary for imaging of ascending aorta with ECG-gated DSCTA.